Human Embryonic-like ECM (hECM) Stimulates Proliferation and Differentiation in Stem Cells While Killing Cancer Cells - Pinney, Emmett (Korean Society for Stem Cell Research, 2011)
BACKGROUND AND OBJECTIVES: There are a number of unique processes seen in the developing fetus that cease post-partum including that tumors rarely form, and scar-less wound healing and digit regeneration occur. In addition, cancer lines have been “reprogrammed” by co-culture with embryonic extracellular matrix (ECM). METHODS AND RESULTS: We have developed a naturally secreted human ECM (hECM) with embryonic-like characteristics which is secreted by neonatal fibroblasts grown in microcarrier suspension cultures under hypoxia. This upregulates a number of substances associated with stem cell niches in the body including various laminins, Collagen 4, CXCL12, NID1, NID2, and NOTCH2. hECM has been shown to support proliferation of hESCs and MSCs and diminish or eliminate tumor load in melanoma (B16), adenocarcinoma (MDA-MB-435), colon cancer (HT29) and glioma (C6) in both in vitro and in vivo animal studies. In the tumor chorioallantoic membrane (tumcam) model hECM significantly inhibited tumor growth and in subcutaneous mouse xenograft experiments, tumor growth was inhibited from 70∼90%. Co-cultures of fibroblasts and mesothelioma show support of fibroblast expansion with a concurrent inhibition of mesothelioma. The inhibitory affect is selective for cancer cells and cancer stem cells through the upregulation of Caspase 9 which forces the cells into apoptosis. CONCLUSIONS: These data show that hECM has the potential to show benefit in the treatment of various cancers as a coating for biopsy needle, tissue filler post tumor removal, and as an injectable into the tumor site.